Nanoparticle-stabilized microemulsions for enhanced oil recovery from heterogeneous rocks. (15th August 2020) - Qin, Tianzhu; Goual, Lamia; Piri, Mohammad; Hu, Zhongliang; Wen, Dongsheng
Graphical abstract: Highlights: Oil displacement in aquifer rock is studied by x-ray microtomography. Novel nanofluid is formed by in-situ synthesis of nanoparticles in microemulsions. Synergistic effects significantly reduce oil droplet size and enhance mobilization. Nanofluid promotes wettability alteration in complex and microporous rock elements. Abstract: Surfactant-stabilized microemulsions (MEs) are often used to reduce the capillary forces responsible for trapping residual oil inside rocks. Recent studies showed that the presence of nanoparticles (NPs) in ME could enhance oil recovery, however their interfacial interactions and the impact of rock characteristics is still unclear. The objective of this study was to understand the effect of microemulsions stabilized by nanoparticles (MENP) on pore-scale fluid displacement mechanisms in a heterogeneous rock such as Arkose. A novel method was developed to synthesize silicon oxide in-situ in a ME. These nanoparticles had less tendency to agglomerate compared to nanopowders and promoted the formation of Pickering emulsions. The impact of ME and MENP on oil displacement in Arkose was examined using microtomography integrated with miniature core flooding. Aged cores were subjected to flooding with different aqueous solutions to investigate the effectiveness of ME and MENP in enhancing oil recovery. We found that ME promoted oil mobilization by reducing IFT and enhancing emulsification. The ability of ME to solubilize adsorbed oil layers contributed to a wettability alteration from oil-wet to weakly water-wet. Therefore, ME could remove 20.0% of additional oil after waterflooding. The incremental oil removal with MENP compared to waterflooding (34.3%) was higher than that of ME due to the emulsification of oil into even smaller droplets where NPs and surfactants synergistically interacted at the interface. The small oil droplets could penetrate small capillary elements of the rock that were inaccessible to ME, leading to stronger wettability alteration especially in carbonate cement.